2005
DOI: 10.1021/ja0522377
|View full text |Cite
|
Sign up to set email alerts
|

Structural Selection by Microsolvation:  Conformational Locking of Tryptamine

Abstract: The conformational space of tryptamine has been thoroughly investigated using rotationally resolved laser-induced fluorescence spectroscopy. Six conformers could be identified on the basis of the inertial parameters of several deuterated isotopomers. Upon attaching a single water molecule, the conformational space collapses into a single conformer. For the hydrogen-bonded water cluster, this conformer is identified unambiguously as tryptamine A. In the complex, the water molecule acts as proton donor with resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
83
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(91 citation statements)
references
References 28 publications
(47 reference statements)
7
83
1
Order By: Relevance
“…Schmitt et al 19 found only six conformers. The "missing" conformer in the latter study can be identified as the C2 band of Philips and Levy.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…Schmitt et al 19 found only six conformers. The "missing" conformer in the latter study can be identified as the C2 band of Philips and Levy.…”
Section: Introductionmentioning
confidence: 98%
“…19 While high quality structure calculations for the electronic ground state are straightforward and bear in general no problems, electronically excited states are much harder to describe with an accuracy comparable to the experiment. Rotationally resolved electronic spectroscopy yields rotational constants which are related to the moments of inertia as primary structural information.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the conformation of the flexible key, which is recognized by the usually more rigid lock, must be quite limited to achieve high selectivity. 6 Indeed, the conformational topography of representative NTs appearing in the gas phase as neutral, [7][8][9][10][11][12][13][14][15][16][17][18][19][20] fluorinated, 21,22 protonated 23,24 and cluster 10,25,26 species was explored by various spectroscopic methods, assisted by quantum chemical calculations. In these studies, comparison of the measured spectral signatures with the calculated spectra enabled one to find the corresponding structures and to unravel their intrinsic properties at the most fundamental level.…”
Section: Introductionmentioning
confidence: 99%